Evaluación del marketing institucional de los Centros Comerciales del Sur de Quito - Lescano Almache, Mayra Fernanda (2014)
The research assesses the institutional marketing handling malls South of Quito, Atahualpa Mall, Ciudad Comercial El Recreo, Quicentro South Mall, after a proposed marketing a generic model is presented. For the realization of this was based on institutional marketing and different marketing strategies.